2020
DOI: 10.1080/20009666.2020.1718478
|View full text |Cite
|
Sign up to set email alerts
|

Physician attire: physicians perspectives on attire in a community hospital setting among non-surgical specialties

Abstract: Background: Several studies have demonstrated a patient preference for physicians wearing a white coat associated with improved patient satisfaction. There are few studies on physicians' perceptions of attire mainly done in the outpatient and surgical specialties. Objective: Assess non-surgical physicians' perception of attire in the hospital and to identify if any difference in the choice of attire amongst generation X and millennial physicians. Methods: We surveyed 86 physicians in the hospital with six sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Throughout medical history, physician attire has affected the doctor patient relationship. Hippocrates is said to have admonished: “The physician must have a worthy appearance; he should look healthy and be well nourished, appropriate to his physique; for most people are of the opinion that those physicians who are not tidy in their own persons cannot look after others well.”[ 9 14 ] Modern culture often depicts physicians on television wearing surgical scrubs in their interactions with patients. In response to rising incidents of hospital acquired infections, some European jurisdictions have imposed policies banning long sleeves, wrist watches and jewelry, also discouraging ties and white coats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout medical history, physician attire has affected the doctor patient relationship. Hippocrates is said to have admonished: “The physician must have a worthy appearance; he should look healthy and be well nourished, appropriate to his physique; for most people are of the opinion that those physicians who are not tidy in their own persons cannot look after others well.”[ 9 14 ] Modern culture often depicts physicians on television wearing surgical scrubs in their interactions with patients. In response to rising incidents of hospital acquired infections, some European jurisdictions have imposed policies banning long sleeves, wrist watches and jewelry, also discouraging ties and white coats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported this issue in several countries including Japan,[ 6 ] Pakistan,[ 7 ] USA,[ 8 9 ] and UK. [ 10 11 ] These reports were using different methodological approaches in separate clinical care scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Physician attire is an important element in establishing patient confidence and trust, 6 enhancing patient comfort when discussing personal problems [7][8][9] and shaping patient perceptions of physician professionalism, 6 intelligence 10 and empathy. 11 Most prior scholarship has focused on a single geographic region, country or clinical context (eg, primary care clinic, hospital setting) [12][13][14][15] and has not considered the relative impacts of different physician specialties, contexts of care, geography and patient factors such as age, education and gender. In addition, heterogeneity among prior studies, such as different sampling methodology and survey instruments, has made comparisons across different studies challenging.…”
Section: Open Accessmentioning
confidence: 99%
“…Although the white coat may serve as a professional symbol and is well respected medicine, it also plays an important role in the layperson's perception of their health care providers. 8 There is little denying that patients prefer their physicians, almost uniformly, to wear a white coat. A systematic review of physician attire that included 30 studies mainly from North America, Europe, and the United Kingdom found that patient preference for formal attire and white coats is near universal.…”
Section: Patient Preference Of Physician Attirementioning
confidence: 99%